Between Truth, Lie and Irony: A Few Remarks on Alethic Modality, Its Exponents and Information Validation - Bojar, Bożenna (Slavic Languages Today: Categories, Structures and Processes, 2021)
This article discusses issues of evaluating information contained in natural language messages, mainly the assessment of their veracity and the exponents of this assessment (alethic modality) in the natural language system and in statements with a meta-information function. The study focuses on grammatical, extrasystemic (intonation, facial expressions, gesture) and situational exponents (joke, metaphor, irony).